Comparative Analysis of Fatty Acid Desaturases in Cyanobacterial Genomes. (19th October 2008) - Chi, Xiaoyuan; Yang, Qingli; Zhao, Fangqing; Qin, Song; Yang, Yu; Shen, Junjun; Lin, Hanzhi
Abstract : Fatty acid desaturases are enzymes that introduce double bonds into the hydrocarbon chains of fatty acids. The fatty acid desaturases from 37 cyanobacterial genomes were identified and classified based upon their conserved histidine-rich motifs and phylogenetic analysis, which help to determine the amounts and distributions of desaturases in cyanobacterial species. The filamentous orN 2 -fixing cyanobacteria usually possess more types of fatty acid desaturases than that of unicellular species. The pathway of acyl-lipid desaturation for unicellular marine cyanobacteria Synechococcus and Prochlorococcus differs from that of other cyanobacteria, indicating different phylogenetic histories of the two genera from other cyanobacteria isolated from freshwater, soil, or symbiont. Strain Gloeobacter violaceus PCC 7421 was isolated from calcareous rock and lacks thylakoid membranes. The types and amounts of desaturases of this strain are distinct to those of other cyanobacteria, reflecting the earliest divergence of it from the cyanobacterial line. Three thermophilic unicellular strains, Thermosynechococcus elongatus BP-1 and two Synechococcus Yellowstone species, lack highly unsaturated fatty acids in lipids and contain only oneΔ 9 desaturase in contrast with mesophilic strains, which is probably due to their thermic habitats. Thus, the amounts and types of fatty acid desaturases are various among different cyanobacterial species, which may result from the adaption to environments in evolution.